4.
a) 3(5a +4) - 6(2 - a)=

b) -4(a - 5) - 3(2 - 3a) =

c) 2m (-3m + 4n) - 3m (4m - 2n)=

d) -7x(2x - y) - 4y(x -2y)=

PROSZE


Odpowiedź :

a) 3(5a+4) - 6(2-a)= 15a+12-12+6a= 21a

b) -4(a-5)-3(2-3a)= -4a+20-6+9a= 5a + 14

c) 2m(-3m+4n)-3m(4m-2n)= -6m²+8mn-12m²+6mn= -18m²+14mn

d) -7x(2x-y)-4y(x-2y)= -14x²+7xy -4xy+8y²= -14x²+3xy+8y²

Mam nadzieję, że pomogłam :)

Odpowiedź:

4)

a) 3 *(5a+ 4) - 6 (2 - a) = 15a + 12 - 12 + 6a = 21a

b) - 4(a - 5) - 3 (2 - 3a) = - 4a + 20 - 6 + 9a = 5a + 14

c) 2m (- 3m + 4n) - 3m (4m - 2n) = - 6m² + 8mn - 12m² + 6mn = - 18m²+ 14mn

d) - 7x (2x - y) - 4y (x - 2y) = - 14x² + 7xy - 4xy + 8y² = - 14x²+ 3xy + 8y²

5)

a) (2a - 7) (a + 4) = 2a² + 8a - 7a - 28 = 2a² + a - 28

b) (- 3x - 5y) (2x + 4y) = - 6x²- 12xy - 10xy - 20y² = - 6x² - 20y² - 22xy

c) (a + 3) (a - 1) + (a - 7) (a + 5) = a² - a + 3a - 3 + a²+ 5a - 7a - 35 = 2a² - 38

d) (m - 4)(5m + 2)- (2m + 3)(4 - 3m) = 5m²+ 2m - 20m - 8 - 8m + 6m²-12 + 9m =

    = 11m² - 17 m - 20

e) (x - 4)² = x² - 4x - 4x + 16 = x² - 8x + 16

 

Szczegółowe wyjaśnienie: